The Effectiveness of the Quartet Card Game in English Vocabulary Mastery for Students at SMP Islam Terpadu Al-Wahidiyah - Siti Nuresa; Muhammad Sood; Nizarrahmadi Nizarrahmadi (Jurnal Pendidikan dan Sastra Inggris, 2025)
Vocabulary mastery is a fundamental aspect of English language skills because it forms the foundation for listening, speaking, reading, and writing. However, in practice, vocabulary learning in the classroom is often conducted monotonously, such as through memorization or written exercises that lack active student participation. This situation has the potential to reduce learning interest and motivation, and impact student learning outcomes. Therefore, innovations in learning strategies are needed to create a more engaging, interactive, and enjoyable learning environment. One alternative learning medium that can be utilized is quartet cards, an educational game that emphasizes student interaction, cooperation, and active involvement in learning and remembering new vocabulary. This study aims to determine the effectiveness of quartet cards in improving English vocabulary mastery at eighth-grade students at Al-Wahidiyah Integrated Islamic Junior High School. The study used a quantitative method with a one-group pre-experimental pretest-posttest design. The sample size was 13 students, selected using a saturated sampling technique. The instrument used was a multiple-choice test administered before and after the treatment. The results showed an increase in the average score from 49.15 in the pretest to 56.38 in the posttest. Further analysis revealed a significant difference between students' abilities before and after using the quartet cards. These findings indicate that the quartet cards are effective in improving junior high school students' English vocabulary mastery. The implication of this study is that English teachers can use the quartet cards as an alternative creative learning strategy that can increase motivation, engagement, and learning outcomes. Furthermore, this research can serve as a basis for developing other educational game-based learning models relevant to students' needs in the modern education era.